2017
DOI: 10.1515/jas-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus Johnsonii AJ5 Metabolites on Nutrition, Nosema Ceranae Development and Performance of Apis Mellifera L.

Abstract: A b s t r a c t The European honey bee (Apis mellifera L.) is known to be affected by such stress factors as pathogen load, poor nutrition and depressed immunity. Nosema ceranae is one of the main parasites that affect colony populations. The relationship between the stress factors and honey bee-bacteria symbiosis appears as an alternative to enhance bee health. The aim of this study was to evaluate the effect of the oral administration of bacterial metabolites produced by Lactobacillus johnsonii AJ5 on nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…A recent field study by De Piano et al (66) showed that honeybee colony performance did not change after administration of Lactobacillus johnsonii AJ5 metabolites. On the other hand, in another field study, administration of a monoculture of Bacillus subtilis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…A recent field study by De Piano et al (66) showed that honeybee colony performance did not change after administration of Lactobacillus johnsonii AJ5 metabolites. On the other hand, in another field study, administration of a monoculture of Bacillus subtilis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…The three species of Lactobacillus isolated from beebread for the first in Jujuy, formed a monophyletic clade separate from bee intestinal strains isolated by other authors in Salta. These last had exhibit beneficial effect to honeybees [4,5,8,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Commercial probiotic preparation also based on lactic acid bacteria were found to be effective against the same parasite [27,36]. Similarly, De Piano et al [39] demonstrated a strong relation between bacterial metabolites and the count of N. ceranae spores, showing a significant decrease after Lactobacillus johnsonii AJ5 administration. Additionally, organic acids produced by lactic acid bacteria present in the honey bee's environment (flowers, beebread, and gut), such as lactic acid, acetic acid, and phenyl-lactic acid, were tested, through feeding, against these microsporidia and showed a strong reduction in spore load in bees [38].…”
Section: Introductionmentioning
confidence: 87%